Gene-therapy in inherited channelopathies like short-QT syndrome: a robust direction towards precision medicine - Hamdani, Nazha; Akın, Ibrahim; El-Battrawy, Ibrahim (European heart journal, 2026)
This editorial refers to ‘AAV9-mediated KCNH2 suppression-replacement gene therapy in a transgenic rabbit model of type 1 short QT syndrome’, by S. Nimani et al., https://doi.org/10.1093/eurheartj/ehaf660.Short-QT Syndrome (SQTS) is an inherited channelopathy first described two decades ago. This disorder is associated with sudden cardiac death, atrial fibrillation, and bradycardia occurring in childhood